Reimplantation and Repeat Infection After Cardiac-Implantable Electronic Device Infections: Experience From the MEDIC (Multicenter Electrophysiologic Device Infection Cohort) Database. (March 2017) - Boyle, Thomas A.; Uslan, Daniel Z.; Prutkin, Jordan M.; Greenspon, Arnold J.; Baddour, Larry M.; Danik, Stephan B.; Tolosana, Jose M.; Le, Katherine; Miro, Jose M.; Peacock, James; Sohail, Muhammad R.; Vikram, Holenarasipur R.; et al.
Abstract : Background—: Infection is a serious complication of cardiovascular-implantable electronic device implantation and necessitates removal of all hardware for optimal treatment. Strategies for reimplanting hardware after infection vary widely and have not previously been analyzed using a large, multicenter study. Methods and Results—: The MEDIC (Multicenter Electrophysiologic Device Infection Cohort) prospectively enrolled subjects with cardiovascular-implantable electronic device infections at multiple institutions in the United States and abroad between 2009 and 2012. Reimplantation strategies were evaluated overall, and every patient who relapsed within 6 months was individually examined for clinical information that could help explain the negative outcome. Overall, 434 patients with cardiovascular-implantable electronic device infections were prospectively enrolled at participating centers. During the initial course of therapy, complete device removal was done in 381 patients (87.8%), and 220 of them (57.7%) were ultimately reimplanted with new devices. Overall, the median time between removal and reimplantation was 10 days, with an interquartile range of 6 to 19 days. Eleven of the 434 patients had another infection within 6 months, but only 4 of them were managed with cardiovascular-implantable electronic device removal and reimplantation during the initial infection. Thus, the repeat infection rate was low (1.8%) in those who were reimplanted. Patients who retained original hardware had a 11.3% repeat infection rate. Conclusions—: Our study findings confirm that a broad range of reimplant strategies are used in clinical practice. They suggest that it is safe to reimplant cardiac devices after extraction of previously infected hardware and that the risk of a second infection is low, regardless of reimplant timing.